Mechanically-enhanced antibacterial dental composite resin and preparation method thereof

By doping modified nanocellulose and octadecyl trimethylammonium chloride in dental composite resins, the problem of insufficient mechanical strength and antibacterial properties of dental composite resins is solved, and a high-strength and efficient antibacterial dental composite resin is achieved , extends service life.

CN119424219APending Publication Date: 2025-02-14SOUTH CHINA UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411574780.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing dental composite resins have insufficient mechanical strength and antibacterial properties in clinical use, resulting in short service life and difficult to effectively prevent secondary problems of tooth decay.

Method used

The nanocellulose modified with silane coupling agent KH570 with a mass fraction of 1-3% and octadecyl trimethylammonium chloride with a mass fraction of 3% was formed by doping in the resin prepolymerization solution. Antibacterial dental composite resin.

Benefits of technology

It has achieved excellent mechanical properties and excellent antibacterial properties of dental composite resin, with a compression strength of 1293MPa, and its antibacterial rate to Streptococcus mutans exceeds 99.99%, extending its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005121503880000011
    Figure HDA0005121503880000011
  • Figure HDA0005121503880000012
    Figure HDA0005121503880000012
  • Figure HDA0005121503880000021
    Figure HDA0005121503880000021
Patent Text Reader

Abstract

The invention belongs to the technical field of dental resin materials, and discloses mechanically-enhanced antibacterial dental composite resin and a preparation method thereof. The antibacterial dental composite resin is prepared by co-doping 1-3% by mass of silane coupling agent KH570 modified nanocellulose and 3% by mass of octadecyl trimethyl ammonium chloride into 93-95% by mass of a resin prepolymer solution, and curing under the action of the balance of an initiator. The invention also discloses a preparation method of the composite resin. The composite resin disclosed by the invention has excellent mechanical property and antibacterial property, and is attractive in appearance and good in biocompatibility; the method is simple and easy to operate, and raw materials are easy to obtain and low in price.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of dental resin material modification, and in particular relates to a mechanically enhanced antibacterial dental resin and a preparation method thereof. Background Art

[0002] Dental caries is currently the most common oral disease in the world. The cause of dental caries is that in the oral environment, clean teeth are wrapped by salivary membranes, and salivary proteins in the salivary layer provide adhesion sites for Streptococcus mutans and other bacteria. Subsequent bacteria gather and multiply to form oral biofilms based on the early adhesion of bacteria. Under bacterial infection, this disease manifests as demineralization of inorganic matter in teeth and decomposition of organic matter, eventually forming cavities. The most effective treatment for this is to fill dental resin restoration prosthetic materials. Light-cured resin has the advantages of beauty, safety and ease of use, making it rapidly developed into an important material for tooth restoration. This type of composite resin is usually composed of a resin matrix and fillers, and different fillers can give the resin different properties. However, the average service life of composite resins used in clinical practice is about 7 years, mainly due to their lack of wear resistance and antibacterial properties. Therefore, improving the mechanical strength and antibacterial properties of composite resins is crucial to extending their service life.

[0003] Some studies have shown that people are currently trying to use inorganic fillers with mesoporous structures to improve mechanical properties through the physical combination of organic and inorganic interfaces, and at the same time introduce antibacterial agents to obtain high-strength and antibacterial composite resins. For example, patent CN 111110572 A points out that mesoporous silica can be used to give the resin high mechanical strength and antibacterial properties. However, due to the hydrophilicity of silica, its dispersibility in the prepolymer liquid of the resin is poor, resulting in a low compressive strength of the composite resin (350-450MPa). There are also related studies showing that it is possible to dope boron nitride, which is second only to diamond in hardness, and add zinc oxide materials as antibacterial agents. However, the preparation process of inorganic fillers such as boron nitride is complicated and expensive; the release process of zinc oxide is slow and the antibacterial effect is poor. The accumulation of various problems makes it impossible to implement the transformation, which is not conducive to large-scale production. Summary of the invention

[0004] The present invention provides a mechanically enhanced antibacterial dental composite resin and a preparation method thereof to solve the problems of fracture and secondary caries during the use of composite resin. The composite resin prepared by the present invention has excellent mechanical properties, excellent antibacterial properties and long-term stability.

[0005] The present invention is achieved through the following technical solutions:

[0006] A mechanically enhanced antibacterial dental composite resin is prepared by doping 1-3% by mass of nanocellulose modified by silane coupling agent KH570 and 3% by mass of octadecyltrimethylammonium chloride into 93-95% by mass of resin prepolymer solution and curing under the action of the remaining initiator.

[0007] The resin prepolymer solution is composed of bisphenol A-glycidyl methacrylate (Bis-GMA) and triethylene glycol dimethacrylate (TEGDMA) in a mass ratio of (1.9-2.1):1, preferably 2:1.

[0008] The initiator is composed of a main initiator, camphorquinone (CQ), and a co-initiator, 4-N,N-ethyl dimethylaminobenzoate (4-EDMAB), in a mass ratio of 1:4.

[0009] The KH570 modified nanocellulose is prepared by the following method: hydrolyzing the silane coupling agent KH570 in water to obtain a modified solution; mixing the aqueous dispersion of nanocellulose, the modified solution and ethanol, and reacting to obtain the KH570 modified nanocellulose.

[0010] The mass ratio of silane coupling agent KH570 to water in the modified solution is (2-3):100;

[0011] The solid content of the nanocellulose dispersion is 0.1-0.6 wt %.

[0012] The mass ratio of nanocellulose to silane coupling agent KH570 is 0.5:(2-3).

[0013] In the reaction system, the mass ratio of ethanol to water is 75%:25%.

[0014] The reaction conditions are room temperature reaction for 20 to 30 hours, pre-freezing, freeze drying, and drying after the reaction.

[0015] The drying condition is to dry in an oven at 110-125° C. for 3-6 hours.

[0016] The method for preparing the mechanically enhanced antibacterial dental composite resin comprises the following steps: mixing nanocellulose modified by silane coupling agent KH570, octadecyltrimethylammonium chloride, resin prepolymer liquid and initiator, initiating polymerization and curing under ultraviolet light to obtain the mechanically enhanced antibacterial dental composite resin.

[0017] The curing condition is irradiation with ultraviolet light having a wavelength of 365-385 nm for 90-120 seconds.

[0018] The mechanically enhanced antibacterial dental composite resin is used for preparing tooth restoration materials.

[0019] The dental composite resin of the present invention has excellent mechanical properties and antibacterial properties. When the addition amount of modified nanocellulose is 2%, the compressive strength is 1410MPa, and when 3% of octadecyl trimethyl ammonium chloride is compounded with 2% of modified nanocellulose, the compressive strength is 1293MPa, and the antibacterial rate of the main oral caries-causing bacteria Streptococcus mutans exceeds 99.99%. Moreover, the nanocellulose used in the present invention can be obtained from wood in nature, the source is ecological and environmentally friendly, the modification process is simple, the required process equipment is simple, the conditions are mild, no toxic reagents are introduced in the preparation process, and the biological safety is high. The added octadecyl trimethyl ammonium chloride is cheap and easy to mass produce.

[0020] Compared with the prior art, the present invention has the following beneficial effects and advantages: the dental composite resin of the present invention has excellent mechanical properties and antibacterial properties, such as a compressive strength of 1293 MPa, and an antibacterial rate of more than 99.99% against Streptococcus mutans, a major oral caries-causing bacterium; and the raw materials of the present invention are ecologically and environmentally friendly, have high biological safety, and are low in price. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 FT-IR images of modified nanocellulose (KCNF) in Examples 5 to 10;

[0022] Figure 2 is the dispersion diagram of modified nanocellulose (KCNF) in Examples 5 to 10;

[0023] Figure 3 TGA and DTG graphs of modified nanocellulose (KCNF) in Examples 5 to 10;

[0024] Figure 4 is the compressive strength curve of the composite resin prepared in Examples 1-10;

[0025] Figure 5 The colony diagram and antibacterial rate of Examples 1, 2, 4, 6, and 9 against Escherichia coli; control-Example 1, 1% STAC-Example 2, 3% STAC-Example 4, 2% KCNF-Example 6, 2% KCNF+3% STAC-Example 9;

[0026] Figure 6 The colony diagrams of Examples 1, 4, 6, and 9 against Streptococcus mutans; control-Example 1, 3% STAC-Example 4, 2% KCNF-Example 6, 2% KCNF+3% STAC-Example 9;

[0027] Figure 7These are resin optical images of Examples 1, 4, 6, and 9, which are Example 1, Example 4, Example 6, and Example 9 from left to right. DETAILED DESCRIPTION

[0028] The present invention will be further described in detail below in conjunction with examples and drawings, but the implementation manner and protection of the present invention are not limited thereto, but are defined by the specification and claims of the present invention.

[0029] Bisphenol A-glycidyl methacrylate: Bis-GMA, triethylene glycol dimethacrylate: TEGDMA, camphorquinone: CQ, 4-N,N-dimethylaminobenzoic acid ethyl ester: 4-EDMAB, octadecyltrimethylammonium chloride: STAC, modified cellulose: KCNF.

[0030] Preparation of modified nanocellulose (KCNF) in Examples 5 to 10:

[0031] (1) 2.17 g of silane coupling agent KH570 was added to 100 ml of deionized water and hydrolyzed under magnetic stirring (600 rpm) at room temperature until no oily substance was left in the solution;

[0032] (2) 100 g of a nanocellulose aqueous dispersion having a solid content of 0.5% was added to the solution in step (1), and 598.5 g of anhydrous ethanol was added to prepare the solution to ethanol: water = 75%: 25%, and stirred at room temperature for 24 h;

[0033] (3) The solution obtained in step (2) was placed in a -20°C refrigerator for pre-freezing for 12 hours overnight, and then placed in a freeze dryer for freeze drying for 3 days. The product was taken out and placed in a 120°C oven for drying for 4 hours. Finally, liquid nitrogen was added to freeze the product and then physically ground to obtain the final product.

[0034] Embodiment 1:

[0035] The pure resin is composed of Bis-GMA, TEGDMA, CQ and 4-EDMAB in a mass percentage ratio of 33%:66%:0.2%:0.8%.

[0036] Preparation of pure resin: 0.825 g Bis-GMA, 1.65 g TEGDMA, 0.005 g CQ and 0.02 g 4-EDMAB were mixed evenly and loaded into a silicone mold supported by a glass slide, and finally photocured for 120 s to obtain pure resin.

[0037] The compressive strength of the pure resin obtained by testing with a universal mechanical testing machine is 1170 MPa. The antibacterial rate of the pure resin against the main oral caries-causing bacteria Streptococcus mutans is set to 0%.

[0038] Embodiment 2:

[0039] The composite resin is composed of Bis-GMA, TEGDMA, STAC, CQ and 4-EDMA in a mass percentage ratio of 32.7%: 65.3%: 1%: 0.2%: 0.8%.

[0040] Preparation of composite resin: 0.82 g Bis-GMA, 1.64 g TEGDMA, 0.025 g STAC, 0.005 g CQ and 0.02 g 4-EDMAB were mixed evenly and loaded into a silicone mold supported by a glass slide, and finally photocured for 120 s to obtain pure resin.

[0041] The compressive strength of the composite resin obtained by the universal mechanical testing machine is 1250MPa. The antibacterial rate of the composite resin to the main oral caries-causing bacteria Streptococcus mutans is 60%.

[0042] Embodiment 3:

[0043] The composite resin is composed of Bis-GMA, TEGDMA, STAC, CQ and 4-EDMA in a mass percentage ratio of 32.3%:64.7%:2%:0.2%:0.8%.

[0044] Preparation of composite resin: 0.8 g Bis-GMA, 1.6 g TEGDMA, 0.05 g STAC, 0.005 g CQ and 0.02 g 4-EDMAB were mixed evenly and loaded into a silicone mold supported by a glass slide, and finally photocured for 120 s to obtain pure resin.

[0045] The compressive strength of the composite resin obtained by universal mechanical testing machine is 1150MPa.

[0046] Embodiment 4:

[0047] The composite resin is composed of Bis-GMA, TEGDMA, STAC, CQ and 4-EDMA in a mass percentage ratio of 32%: 64%: 3%: 0.2%: 0.8%.

[0048] Preparation of composite resin: 0.8 g Bis-GMA, 1.6 g TEGDMA, 0.074 g STAC, 0.005 g CQ and 0.02 g 4-EDMAB were mixed evenly and loaded into a silicone mold supported by a glass slide, and finally photocured for 120 s to obtain pure resin.

[0049] The compressive strength of the composite resin obtained by the universal mechanical testing machine is 1100MPa. The antibacterial rate of the composite resin against the main oral caries-causing bacteria Streptococcus mutans is 99.99%.

[0050] Embodiment 5:

[0051] The composite resin is composed of Bis-GMA, TEGDMA, KCNF, CQ and 4-EDMA in a mass percentage ratio of 32.7%: 65.3%: 1%: 0.2%: 0.8%.

[0052] Preparation of composite resin: 0.82 g Bis-GMA, 1.64 g TEGDMA, 0.025 g KCNF, 0.005 g CQ and 0.02 g 4-EDMAB were mixed evenly and loaded into a silicone mold supported by a glass slide, and finally photocured for 120 s to obtain pure resin.

[0053] The compressive strength of the composite resin obtained by universal mechanical testing machine is 1210MPa.

[0054] Embodiment 6:

[0055] The composite resin is composed of Bis-GMA, TEGDMA, K-CNF, CQ and 4-EDMA in a mass percentage ratio of 32.3%: 64.6%: 2%: 0.2%: 0.8%.

[0056] Preparation of composite resin: 0.8 g Bis-GMA, 1.6 g TEGDMA, 0.05 g K-CNF, 0.005 g CQ and 0.02 g 4-EDMAB were mixed evenly and loaded into a silicone mold supported by a glass slide, and finally photocured for 120 s to obtain pure resin.

[0057] The compressive strength of the composite resin obtained by the universal mechanical testing machine is 1410MPa. The antibacterial rate of the composite resin to the main oral caries-causing bacteria Streptococcus mutans is 0%.

[0058] Embodiment 7:

[0059] The composite resin is composed of Bis-GMA, TEGDMA, KCNF, CQ and 4-EDMA in a mass percentage ratio of 32%: 64%: 3%: 0.2%: 0.8%.

[0060] Preparation of composite resin: 0.8 g Bis-GMA, 1.6 g TEGDMA, 0.075 g KCNF, 0.005 g CQ and 0.02 g 4-EDMAB were mixed evenly and loaded into a silicone mold supported by a glass slide, and finally photocured for 120 s to obtain pure resin.

[0061] The compressive strength of the composite resin obtained by universal mechanical testing machine is 1316MPa.

[0062] Embodiment 8:

[0063] The composite resin is composed of Bis-GMA, TEGDMA, KCNF, STAC, CQ, and 4-EDMA in a mass percentage ratio of 31.7%: 63.4%: 1%: 3%: 0.2%: 0.8%.

[0064] Preparation of composite resin: 0.79 g Bis-GMA, 1.58 g TEGDMA, 0.025 g T-CNF, 0.075 g STAC, 0.005 g CQ and 0.02 g 4-EDMAB were mixed evenly and loaded into a silicone mold supported by a glass slide, and finally photocured for 120 s to obtain pure resin.

[0065] The compressive strength of the composite resin obtained by universal mechanical testing machine is 1310MPa.

[0066] Embodiment 9:

[0067] The composite resin is composed of Bis-GMA, TEGDMA, KCNF, STAC, CQ, and 4-EDMA in a mass percentage ratio of 31.3%: 62.7%: 2%: 3%: 0.2%: 0.8%.

[0068] Preparation of composite resin: 0.78 g Bis-GMA, 1.56 g TEGDMA, 0.05 g T-CNF, 0.075 g STAC, 0.005 g CQ and 0.02 g 4-EDMAB were mixed evenly and loaded into a silicone mold supported by a glass slide, and finally photocured for 120 s to obtain pure resin.

[0069] The compressive strength of the composite resin obtained by the universal mechanical testing machine is 1293MPa. The antibacterial rate of the composite resin against the main oral caries-causing bacteria Streptococcus mutans is 99.99%.

[0070] Embodiment 10:

[0071] The composite resin is composed of Bis-GMA, TEGDMA, KCNF, STAC, CQ and 4-EDMA in a mass percentage ratio of 31%:62%:3%:3%:0.2%:0.8%.

[0072] Preparation of composite resin: 0.775 g Bis-GMA, 1.55 g TEGDMA, 0.075 g T-CNF, 0.075 g STAC, 0.005 g CQ and 0.02 g 4-EDMAB were mixed evenly and loaded into a silicone mold supported by a glass slide, and finally photocured for 120 s to obtain pure resin.

[0073] The compressive strength of the composite resin obtained by universal mechanical testing machine is 1210MPa.

[0074] Figure 1 FT-IR images of modified nanocellulose (KCNF) in Examples 5 to 10 of the present invention; Figure 2 is a dispersion diagram of modified nanocellulose (KCNF) in Examples 5 to 10 of the present invention; Figure 3 These are TGA and DTG graphs of the modified nanocellulose (KCNF) in Examples 5 to 10 of the present invention. CNF represents unmodified nanocellulose. Figure 2 T=30min indicates the dispersion of the modified nanofibers after being placed for 30 minutes.

[0075] Figure 4 The compressive strength curves of the composite resins prepared in Examples 1-10.

[0076] Figure 5 The colony diagram and antibacterial rate of Examples 1, 2, 4, 6, and 9 against Escherichia coli; control-Example 1, 1% STAC-Example 2, 3% STAC-Example 4, 2% KCNF-Example 6, 2% KCNF+3% STAC-Example 9.

[0077] Figure 6 These are the colony images of Examples 1, 4, 6, and 9 against Streptococcus mutans; control-Example 1, 3% STAC-Example 4, 2% KCNF-Example 6, 2% KCNF+3% STAC-Example 9.

[0078] Depend on Figure 1 It can be seen that the synthesized KCNF has many different absorption peaks from CNF. -1 The absorption peak at 1598 cm -1 The absorption peak at 1715 cm is caused by the bending vibration of -OH in water molecules adsorbed from the air on the surface of nanocellulose. -1 The absorption peak at 1598cm is the carbonyl of methacryloyl in KH570, but the absorption peak at 1598cm -1 The transmission signal intensity at 3346 cm-1 was significantly reduced, indicating that the surface hydrophobicity of the modified cellulose nanocrystals was enhanced, reducing their tendency to adsorb water molecules. -1 The absorption peak at 1050-1170cm is the absorption peak of -OH; -1 The Si-O-Si and Si-OC absorption bands at the sites overlap with the strong COC vibration bands in cellulose nanocrystals, so it is difficult to detect them. Infrared analysis shows that the modification of KCNF is successful. Figure 2 It can be seen that by Figure 2It can be seen that the unmodified CNF can be well dispersed in water, but cannot be dispersed in the oily resin prepolymer solution and will precipitate out in the form of precipitation; however, the modified KCNF can be well dispersed in the resin prepolymer solution and is difficult to disperse in water, which also confirms the success of the hydrophobic modification. Figure 3 The TGA graph on the left shows that the rapid decrease in mass at 300°C is caused by the breakage of the cellulose molecular chain at high temperature. The mass loss within 400°C is mainly due to the thermal degradation of the silane coupling agent molecular chain. Figure 3 The DTG graph on the right side shows that the silane coupling agent molecules coated on the CNF surface can hinder the breakage and thermal decomposition of cellulose molecular chains, delaying and greatly reducing its maximum weight loss rate, thereby improving the thermal stability of CNF, indicating that the modification was successful.

[0079] Depend on Figure 4 It can be seen that the addition of STAC will affect the mechanical properties of the resin, but the addition of KCNF can enhance the mechanical properties of the resin. 2% CNF is the best addition amount, and the mechanical properties begin to decline at 3% CNF, which may be because too much KCNF destroys the structure of the resin. Figure 5 and Figure 6 It can be seen that with the addition of the antibacterial agent STAC, a content of 3% can achieve a good antibacterial effect. Therefore, after considering the advantages and disadvantages of the two, 2% KCNF and 3% STAC were selected as the final product. In summary, the present invention uses modified nanocellulose and quaternary ammonium salt as dopants to fill into the resin. The KCNF with a simple preparation process and the inexpensive quaternary ammonium salt STAC can effectively enhance the mechanical strength and antibacterial properties of dental resins.

[0080] Figure 7 The optical images of the resins of Examples 1, 4, 6 and 9 are shown in order from left to right: Example 1, Example 4, Example 6 and Example 9. The resin prepared by the present invention becomes a transparent resin after being left to stand.

[0081] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A mechanically enhanced antibacterial dental composite resin, characterized in that: The nanocellulose modified by silane coupling agent KH570 with a mass fraction of 1-3% and octadecyltrimethylammonium chloride with a mass fraction of 3% are doped into a resin prepolymer liquid with a mass fraction of 93-95%, and solidified under the action of the remaining initiator; The resin prepolymer liquid is composed of bisphenol A-glycidyl methacrylate and triethylene glycol dimethacrylate in a mass ratio of (1.9-2.1):

1.

2. The mechanically reinforced antibacterial dental composite resin according to claim 1, characterized in that: The initiator is composed of a main initiator, camphorquinone, and a co-initiator, 4-N,N-dimethylaminobenzoic acid ethyl ester, in a mass ratio of 1:

4.

3. The mechanically reinforced antibacterial dental composite resin according to claim 1, characterized in that: The KH570 modified nanocellulose is prepared by the following method: hydrolyzing the silane coupling agent KH570 in water to obtain a modified solution; mixing the aqueous dispersion of nanocellulose, the modified solution and ethanol, and reacting to obtain the KH570 modified nanocellulose.

4. The mechanically reinforced antibacterial dental composite resin according to claim 3, characterized in that: The solid content of the aqueous dispersion of nanocellulose is 0.1 to 0.6 wt %; The mass ratio of nanocellulose to silane coupling agent KH570 is 0.5:(2-3); In the reaction system, the mass ratio of ethanol to water is 75%:25%.

5. The mechanically reinforced antibacterial dental composite resin according to claim 3, characterized in that: The mass ratio of silane coupling agent KH570 to water in the modified solution is (2-3):100; the hydrolysis refers to hydrolysis until there is no oily substance; The reaction conditions are as follows: reacting at room temperature for 20 to 30 hours; pre-freezing, freeze drying, and drying after the reaction.

6. The method for preparing the mechanically reinforced antibacterial dental composite resin according to any one of claims 1 to 5, characterized in that: The following steps are involved: Nanocellulose modified by silane coupling agent KH570, octadecyltrimethylammonium chloride, resin prepolymer solution and initiator are mixed evenly, and polymerization and curing are initiated under ultraviolet light to obtain a mechanically enhanced antibacterial dental composite resin.

7. The method for preparing the mechanically enhanced antibacterial dental composite resin according to claim 6, characterized in that: The curing condition is irradiation with ultraviolet light having a wavelength of 365-385 nm for 90-120 seconds.

8. The use of the mechanically reinforced antibacterial dental composite resin according to any one of claims 1 to 5, characterized in that: The mechanically enhanced antibacterial dental composite resin is used for preparing tooth restoration materials.